ANALYSIS OF CONTROL SYSTEM MODIFICATIONS ON COAL FEEDER MOTORS TO ACCELERATE MILL RECOVERY DURING COAL BLOCKING DISTURBANCES - Erwin Harahap; Solly Aryza; Adi Sastra P Tarigan (INFOKUM, 2022)
Coal feeder is one of the main tools in a Steam Power Plant (PLTU) which is used to regulate the rate of coal. The coal feeder is in charge of controlling the amount of coal that enters the mill according to the needs of the fuel used in the boiler. The feeder is the main equipment in the power plant that functions in regulating the rate of coal from the coal bunker. This study aims to determine the cause of the Emergency Diesel Generator when it fails to start, modification of the Emergency Diesel Generator work system and Emergency performance. From the results of the research, it was tested that the implementation of the control system modification in accelerating mill recovery when there was a caol blocking disturbance at the PLTU in unit 1 in Pangkalan Susu. The conclusion of this study aims at the reliability of the coal unit. The cleaning process becomes easier and more efficient to maximize. .